Spiders (Arachnida: Araneae) in the semideciduous Atlantic Forest : An ecological and morphological trait dataset for functional studies - Munévar, Ana Katerinne (2020)
Fil: Munévar, Ana Katerinne. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Biología Subtropical (Puerto Iguazú); Argentina.